1978
DOI: 10.1113/jphysiol.1978.sp012400
|View full text |Cite
|
Sign up to set email alerts
|

Potassium efflux in heart muscle during activity: extracellular accumulation and its implications.

Abstract: SUMMARY1. Extracellular K+ activity and transmembrane potential were simultaneously monitored with a K+-selective micro-electrode placed in the extracellular space and a standard KCl-filled micro-electrode in the intracellular space of the frog ventricular muscle.2. K+ was found to accumulate during activity and had the approximate magnitude and time course to account for the measured membrane depolarization.3. The magnitude of the K+ accumulation depended on the frequency of stimulation, diameter of the muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 28 publications
7
76
0
Order By: Relevance
“…It is therefore reasonable to postulate that the accumulation of K+ during the action potential would have little effect on the shape or the time course of the plateau at the postive membrane potentials. In this respect it has been shown that the rate of K accumulation during the action potential plateau, as measured with K-selective micro-electrodes, does not change when the [K]o was altered (Kline & Morad, 1978). On the other hand, as the plateau repolarizes toward -20 mV the inwardly rectifying K current becomes more dominant and initiates the rapid repolarization.…”
Section: Discussionmentioning
confidence: 97%
“…It is therefore reasonable to postulate that the accumulation of K+ during the action potential would have little effect on the shape or the time course of the plateau at the postive membrane potentials. In this respect it has been shown that the rate of K accumulation during the action potential plateau, as measured with K-selective micro-electrodes, does not change when the [K]o was altered (Kline & Morad, 1978). On the other hand, as the plateau repolarizes toward -20 mV the inwardly rectifying K current becomes more dominant and initiates the rapid repolarization.…”
Section: Discussionmentioning
confidence: 97%
“…They have suggested that such shifts are mediated by accumulations of K+ in the restricted spaces between individual Purkinje cells. There is evidence for a K+ accumulation in the less restricted spaces between ventricular cells (Kline & Morad, 1978), so that any explanation may be common to the two tissues. Brown et al (1978) proposed three ways whereby an acidosis could lead to K+ accumulation: (1) inhibition of the Na+-K+ pump, (2) modification of the sarcolemmal K+ permeability, (3) reduction in the fixed negative charge between the intercellular clefts.…”
Section: Ca2+/h+ Competition and Tensionmentioning
confidence: 99%
“…Thermal modulation of excitation may involve the accumulation of K + ions in the intercellular space and frequency-dependent changes in the amplitude of ion currents (Kline and Morad, 1978), which should be taken into account in experimental procedures. Comparison of results from isolated cells, spontaneously active multicellular preparations (sinoatrial tissues, working whole hearts) and in vivo ECG recordings would help to elucidate the significance of molecular and cellular mechanisms in the thermal response of the whole heart Badr et al, 2016).…”
Section: Temperature-dependent Depression Of Electrical Excitationmentioning
confidence: 99%